PENERAPAN RESPONSIBILITAS KERJA DALAM MENINGKATKAN KINERJA APARATUR PELAYANAN PUBLIK DI KANTOR PERTANAHAN HALMAHERA BARAT - MEDJA, AGNESIA AGUSTIN; ROMPAS, WELSON; KOLONDAM, HELLY (JURNAL ADMINISTRASI PUBLIK, 2020)
Work responsibility is a measure to see government administrators carry out the authority they give and carry out in accordance with existing procedures and provisions, public bureaucracy is said to be responsible if they carry out their duties as well as possible and are not just reasons, whether someone is supervising or not, by mobilizing all abilities it has effectively and efficiently. This study aims to explain the application of work responsibility in improving the performance of public service personnel. To achieve these objectives researchers used qualitative methods using data collection techniques through interview, observation, and documentation. The result of research in the land office west Halmahera show that all staff employes can be responsible for carrying out their positions, they can carry out the authority given to them by their superiors, there are performance evaluation standards, the servives provided to the community are good enough, agencies take service actions fair according to the work code of ethics, and there is a commitment from the leadership by providing quality public service and having fast, easy, and clear procedures so that people are satisfied in completing their affairs. So that all staff can provide better service,it is hoped that the office building will be repaired and make improvements in strengthening the internet network. Keywords: Work Responsibility, Performance, Public Service.